REVITALISASI BAHASA DAERAH DI ERA DIGITAL: STUDI KASUS PENGGUNAAN BAHASA JAWA DALAM INTERAKSI KOMUNIKATIF PADA GRUP WHATSAP KARAWITAN UIN RADEN MAS SAID SURAKARTA - Dilfam Aldisya Ervani; Riska Harist Hammami; Ragil Nur Safitri (2025)
Javanese, as one of the largest regional languages in Indonesia, faces the challenge of declining usage, especially among the younger generation due to the influence of globalization and the dominance of national and foreign languages in digital communication. This research aims to sociolinguistically examine WhatsApp group conversations using Janet Holmes’ theory. Furthermore, this research also examines the use of WhatsApp as a digital communication tool for gamelan (karawitan) from McQuail’s perspective. It also examines in-depth efforts to preserve (revitalize) Javanese amidst the rapid influx of foreign languages and slang using the Grenoble and Whaley approach. Using communication ethnography and digital discourse analysis, this descriptive qualitative research collected data through conversation documentation and participant observation of community members. The results show that Javanese remains dominant in the community’s daily qq0communication, functioning not only as a communication tool but also as a medium for preserving culture and identity. The use of digital humor, stickers, and adaptation of vocabulary meanings enrich the dynamics of community interactions across generations and linguistic diversity. Private media such as WhatsApp has proven effective in supporting the sustainability of regional languages through intense and authentic communication. This study concludes that the use of private digital media such as WhatsApp can be an innovative strategy in revitalizing the Javanese language and preserving cultural values in the digital era.